Structure-functional analysis of a novel cell wall modifying autoproteolytic enzyme and crystallographic fragment screening for Schistosoma mansoni purine nucleotide phophorylases - Faheem, Muhammad (2016)
Metagenomics techniques are now widely used for the search of new valuable enzymes of interest and other biotechnological products. Sophistication in the second-generation sequencing has significantly facilitated metagenomics technique for collection of huge amount of microbial genomic data. One of the current focuses in science is to seek the interpretation and transformation of the collected genomic data into functional proteomics data. Combination of structural biology and genomic data is one way to achieve such goal. In this study we have assessed a novel bacterial protein selected on a screen for activity on carbohydrates in a microbial metagenomic library from the gut of Capra hircus. Initial sequence analysis of the open reading frame (ORF) for this selected novel bacterial protein indicated that it could be annotated as an uncharacterized novel bacterial cell wall modifying enzyme. Sequence analysis of the protein has shown that it carries three domains: an N-terminus cysteine protease, a peptidoglycan binding (PGBD) and a C-terminus Src-Homology 3 (SH3) bacterial domain. Later with homology modeling we have observed that it carries an additional N-terminus domain with LCI fold. We have successfully cloned, expressed and purified this Capra hircus putative cysteine protease (PCP). Autoproteolytic activity has been observed for PCP, which was inhibited with protease inhibitors cocktail. We have observed that the autoproteolytic activity is carried either by the second or third domain of PCP. This protein has shown cell wall hydrolytic activity and ampicillin binding capacity, a characteristic of most of bacterial cell wall modifying enzymes. Ampicillin binding to PCP was further evaluated with fluorimetric analysis. PCP structure was modeled by homology modeling with good validation statistics and in agreement with circular dichroism data. The domains of PCP have conserved LCI, Cysteine, histidine-dependent amidohydrolase/peptidase (CHAP), PGBD and SH3 folds. It has a conserved active site dyad, Cys100 and His161, which is a signature of cysteine proteases. Furthermore, the overall architecture of the model was assembled in SAXS generated density map. Initial protein crystals are also obtained for the last two domains, which diffracted to very low resolution.